Infinite cosmos : visions from the James Webb Space Telescope - Siegel, Ethan, 1978- (Washington, D.C. : National Geographic, 2024)
"This book recounts the science and history of the James Webb Space Telescope, with stunning images"--
Design & construction -- Launch & deployment -- Sights & science.
Includes index.
Keywords: James Webb Space Telescope (Spacecraft) -- History; Space astronomy -- History